Metallic-semiconducting junctions create sensing hot-spots in carbon nanotube FET aptasensors near percolation - Thanihaichelvan, M.; Browning, L.A.; Dierkes, M.P.; Reyes, R.M.; Kralicek, A.V.; Carrahere, C.; Marlow, C.A.; Plank, N.O.V. (University of Jaffna, 2019)
Easily fabricated random network carbon nanotube field-effect transistors (CNT-FETs) have benefitted from improved separation techniques to deliver CNTs with current formulations providing at least 99% semiconducting tube content. Amongst the most promising applications of this device platform are electronic biosensors, where the network conduction is affected through tethered probes such as aptamers which act as molecular scale electrostatic gates. However, the prevailing assumption that these biosensor devices would be optimized if metallic tubes were entirely eliminated has not been examined. Here, we show that metallic-semiconducting junctions in aptasensors are sensing hotspots and that their impact on sensing is heightened by the CNT network’s proximity to percolation. First, we use a biased conducting AFM tip to gate a CNT-FET at the nanoscale and demonstrate that the strongest device response occurs when gating at metallic-semiconducting junctions. Second, we resolve the target sensitivity of an aptasensor as a function of tube density and show heightened sensitivity at densities close to the percolation threshold. We find the strongest sensing response where the 1% of metallic tubes generate a high density of metallic semiconducting junctions but cannot form a percolated metallic path across the network. These findings highlight the critical role of metallic tubes in CNT-FET biosensor devices and demonstrate that network composition is an important variable to boost the performance of electronic biosensors.
Keywords: CNT network; FET; Electrostatic gating; Aptasensor; Percolation